This is not a game - Mullen, Kelly (New York : Dutton, 2025)
"Widow Mimi lives on idyllic Mackinac Island where cars are not allowed and a Gibson with three onions at the witching hour is compulsory. Her granddaughter, Addie, is getting over the heartbreak of her fianče, Brian, dumping her and cutting her out of the deal for the brilliantly successful video game, Murderscape, they invented together (with Addie doing most of the heavy lifting). When Mimi gets an invitation from local socialite Jane Ireland--a seventysomething narcissist who is having an affair with her son-in-law--to a charity auction, it is the perfect excuse to get Addie to join her for the weekend. What Mimi isn't telling Addie is that a blackmail threat from Jane looms over the party's invitation. In case the scene wasn't already set for a turbulent weekend, a big storm rolls in, trapping everyone in the mansion. And then, Jane's body is found. Soon Mimi and Addie are caught in a dangerous game, relying on their skills (Mimi loves a crossword puzzle, and Addie is a brilliant game designer, after all) to narrow down the suspects. When another body turns up, the sleuthing pair realize someone else is playing a deadly game, and they might not survive the night." -- Publisher annotation.
Keywords: Grandmothers -- Fiction; Murder -- Investigation -- Fiction; Parties -- Fiction; Detective and mystery fiction; Novels